OPTIMIZATION OF PALLIATIVE CHEMOTHERAPY AND IMPROVEMENT OF QUALITY OF LIFE IN PATIENTS WITH BREAST CANCER ACCOMPANIED BY PULMONARY METASTASES: A STRUCTURED LITERATURE REVIEW (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Pulmonary metastases are frequently observed in advanced breast cancer and significantly contribute to morbidity and mortality. Palliative chemotherapy remains an essential component of treatment, aiming to control disease progression, alleviate symptoms, and maintain quality of life.Objective: To analyze contemporary evidence regarding optimization of palliative chemotherapy and quality-of-life improvement in patients with breast cancer accompanied by pulmonary metastases.Materials and Methods: A structured literature review was conducted using publications indexed in PubMed, Scopus, Web of Science, and Google Scholar. Studies published between 2015 and 2025 addressing palliative chemotherapy, metastatic breast cancer, pulmonary metastases, supportive care, and quality-of-life outcomes were included.
Keywords: Breast cancer, pulmonary metastases, palliative chemotherapy, quality of life, metastatic breast cancer, supportive care, oncology